2021
DOI: 10.1111/eci.13579
|View full text |Cite
|
Sign up to set email alerts
|

Vascular growth factors as potential new treatment in cardiorenal syndrome in diabetes

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 99 publications
(132 reference statements)
0
6
0
Order By: Relevance
“…It has been reported that diminished endothelial density is a common phenomenon in the kidney of I/R-induced AKI ( Wu et al, 2021 ), whereas increased expression of VEGFA and in its receptor VEGFR2 is associated with renal neovascularization ( Ricciardi and Gnudi, 2021 ). To further explore whether MSCs-derived exosomes would protect against AKI via regulating renal angiogenesis in the pig model of AKI, we examined the effect of exosomes on the expression of VEGFA and VEGFR2 in the kidney.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that diminished endothelial density is a common phenomenon in the kidney of I/R-induced AKI ( Wu et al, 2021 ), whereas increased expression of VEGFA and in its receptor VEGFR2 is associated with renal neovascularization ( Ricciardi and Gnudi, 2021 ). To further explore whether MSCs-derived exosomes would protect against AKI via regulating renal angiogenesis in the pig model of AKI, we examined the effect of exosomes on the expression of VEGFA and VEGFR2 in the kidney.…”
Section: Resultsmentioning
confidence: 99%
“…An independent role of Angpt2 in predicting adverse cardiorenal outcomes in patient with diabetes, coronary artery disease and HF has been described [ 46 ]. An increased Angpt2/Angpt1 ratio in the myocardium favors endothelium apoptosis and inflammation, which have been associated with the severity of renal impairment and albuminuria [ 47 ].…”
Section: Pathophysiology Of Cardiorenal Syndromementioning
confidence: 99%
“…Inhibition of the increased VEGFA production in DN have so far been frustrating, with severe adverse effects [ 59 ] including glomerular thrombotic microangiopathy [ 60 , 61 ]. However potential new approaches may be feasible [ 62 ]. Recent experimental studies [ 63 ] have described a reduction of podocytic VEGF by SLGT2 inhibition.…”
Section: Histopathology and Therapeutic Optionsmentioning
confidence: 99%